Exploring the Link Between Creativity and Entrepreneurial Intentions: Evidence from Design Student at Universitas XYZ, Tangerang, Indonesia - Aristo, Benny; Duque, Joshua C.A.T. (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
This research investigates the correlation between creativity and the aspiration to pursue entrepreneurship, an essential area for individuals looking to innovate and create new products or services. The focus is on understanding how creativity, coupled with the willingness to take risks and entrepreneurial self-confidence, influences the intention to start a business. Utilizing a quantitative methodology, data was collected from 184 design students at Universitas XYZ located in Tangerang Indonesia. The study employs structural equation modelling to examine the construct relationships within the theoretical framework, with SmartPLS v.4.0.8.4 used for data analysis. The results indicate that entrepreneurial self-confidence significantly predicts the intention to become an entrepreneur. However, creativity and the tendency to take risks do not show a significant impact on entrepreneurial aspirations. This research contributes to the existing body of knowledge on the factors driving entrepreneurial intentions and details the relationship between creativity and the desire to embark on an entrepreneurial journey. The findings have significant implications for the design of programs aimed at fostering entrepreneurial skills